The American path of bourgeois development - Gaido, Daniel (2002)
The peculiarities of American political, social and intellectual development have been determined by the fact that, economically speaking, the United States was a colonial country during the first three centuries of its existence, and that, towards the end of the nineteenth and the beginning of the twentieth century, it effected on almost direct transition from a colonial to an imperialist economy. The aim of this article is to analyse, from the point of view of the labour theory of value, the way in which the American regime of landed property (the so-called `frontier') influenced the development of capitalism during what should properly be called, adopting as our taxonomic criterion the prevailing social relations of production, the colonial period of American history. - Reproduced.
Keywords: Middle class - United States; Capitalism - United States; Capitalism